New OB star candidates in the Carina Arm around Westerlund 2 from VPHAS+. Issue 4 (19th May 2015) - Mohr-Smith, M.; Drew, J. E.; Barentsen, G.; Wright, N. J.; Napiwotzki, R.; Corradi, R. L. M.; Eislöffel, J.; Groot, P.; Kalari, V.; Parker, Q. A.; Raddi, R.; Sale, S. E.; et al.
Abstract : O and early B stars are at the apex of galactic ecology, but in the Milky Way, only a minority of them may yet have been identified. We present the results of a pilot study to select and parametrize OB star candidates in the Southern Galactic plane, down to a limiting magnitude of g = 20. A 2 deg 2 field capturing the Carina Arm around the young massive star cluster, Westerlund 2, is examined. The confirmed OB stars in this cluster are used to validate our identification method, based on selection from the ( u − g, g − r ) diagram for the region. Our Markov Chain Monte Carlo fitting method combines VPHAS+ u, g, r, i with published J, H, K photometry in order to derive posterior probability distributions of the stellar parameters log ( T eff ) and distance modulus, together with the reddening parameters A 0 and R V . The stellar parameters are sufficient to confirm OB status while the reddening parameters are determined to a precision of σ( A 0 ) ∼ 0.09 and σ( R V ) ∼ 0.08. There are 489 objects that fit well as new OB candidates, earlier than ∼B2. This total includes 74 probable massive O stars, 5 likely blue supergiants and 32 reddened subdwarfs. This increases the number of previously known and candidate OB stars in the region by nearly a factor of 10. Most of the new objects are likely to be at distances between 3 and 6 kpc. We have confirmed the results of previous studies that, at these longer distances, these sight lines require non-standard reddening laws with 3.5 < R V < 4.